2008
DOI: 10.1002/mds.22220
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic movement disorders in children

Abstract: Psychogenic movement disorders (PMDs) are well characterized in adults, but childhood-onset PMDs have not been extensively studied. We reviewed the medical records of children who were diagnosed in our clinic with PMDs since 1988 and identified 54 patients with PMDs, representing 3.1% of our pediatric movement disorder population and 5.7% of all PMD cases. The mean age at symptom onset was 14.2 years (+/-2.11, range 7.6-17.7). Similar to published data in adults, two-thirds of children exhibited multiple PMD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
136
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(145 citation statements)
references
References 44 publications
3
136
3
3
Order By: Relevance
“…2,17 As anticipated, PMDs were more common in female adolescents. Interestingly, 9 of 12 children with PMDs had comorbid psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…2,17 As anticipated, PMDs were more common in female adolescents. Interestingly, 9 of 12 children with PMDs had comorbid psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 60%
“…PMD assumed a generalized distribution in many participants, but when localized affected the dominant limb. 2,17 PMD is also associated with a high incidence of gait disturbance, headache, and other neurological symptoms. 17 The diagnosis of PMD requires a constellation of these characteristics because the diagnosis based on the existence of a single feature is not infallible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychogenic dropped head, especially associated with other movement disorders, has not yet been reported in children 2,4 . Although assessment of PMDs can be complex in childhood, our case showed that assessment of clinical features combined with therapeutic intervention (placebo test) may be useful for PMDs diagnosis 1,3,5 .…”
mentioning
confidence: 91%